Distribution of ABO Blood Group System, Presentations, Comorbidities, Disease Severity and Outcome of COVID- 19 Patients in Jashore, Bangladesh - Acherjya, Goutam Kumar; Ali, Mohammad; Tarafder, Keya; Paul, Shuprio; Mou, Sharmin Sultana; Kar, Subrata Prokash; Dutta, Debasish; Sarker, Marufa; Sultana, Afroza; Roy, Gobinda Chandra; Kabir, Ahmedul (Journal of Bangladesh College of Physicians and Surgeons, 2022)
Introduction: The whole world has been crippled by COVID- 19 for a long period of time and a lot of its issues still remain unknown. The study was designed to assess the distribution of ABO blood group system, presentation, comorbidities, disease severity and outcome of COVID-19 patients in Jashore, Bangladesh. Methods: This retrospective type of observational study recruited 928 RT-PCR positive COVID-19 patients above 18 years living in the district of Jashore, Bangladesh. Results: Mean age of the study population was 41.55±13.59 years including a significant age difference (p: <0.001) in disease severity and insignificant gender difference were observed (p: 0.291). Fever was frequently presenting symptoms (83.1%) in our study associated with cough 47.1%, fatigue 39.2%, myalgia 38.0%, distaste 35.3%, anosmia or hyposmia 33.3%. Diabetes (p: <0.001), hypertension (p: <0.001), chronic respiratory illness (p: <0.001), coronary artery diseases (p: 0.003) and malignancy (p: 0.003) played as potential risk factors for developing COVID-19 severity. Out of the total study patients, 36.9%, 29.1%, 22.5 and 11.5% COVID- 19 patients came from blood B, O, A an AB respectively. On the other hand 95.5% COVID-19 patients were Rhesus positive. However, we did not found any significant association between disease severity and different ABO and Rh blood group (p: 0.379 and p: 0.092 respectively). A 97.6% of our patients had significantly (p: <0.001) been recovered from COVID-19 where most of the patients (81.1%) were managed at home. Though, 2% and 1.9% of our patients developed severe pneumonia and critically ill COVID-19, we had noticed significantly low mortality rate (1.4%, p: <0.001) in this current study. Conclusion: In this recent study, blood group B constituted the highest number of the COVID-19 patients. Fever, cough and fatigue were the most common presenting feature of COVID-19 patients. Preexistent diabetes, hypertension, chronic respiratory diseases, coronary artery diseases and malignancy played as significant potential risk factors of diease severity of COVID-19. A majority of the patients were significantly managed at home. A minimum portion of the COVID-19 patients developed severe pneumonia and critical illness; and a significant low case fatality occurred in our study. J Bangladesh Coll Phys Surg 2022; 40: 246-252